2019
DOI: 10.1128/jvi.00087-19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Previous Respiratory Syncytial Virus Infection on Murine Immune Responses to F and G Protein-Containing Virus-Like Particles

Abstract: Most individuals are infected with respiratory syncytial virus (RSV) by age two, but infection does not result in long-term protective immunity to subsequent infections. Previous RSV infection may, however, impact responses to an RSV vaccine. The goal of these studies was to explore the effect of previous RSV infection on murine antibody responses to RSV F and G protein-containing virus-like particles (VLP), comparing responses to those resulting from VLP immunization of RSV-naive animals. These studies showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
(86 reference statements)
4
9
0
Order By: Relevance
“…An important property of vaccines is the durability of protective antibodies, but many vaccines do not result in a long duration of protection. We have previously reported that VLPs with RSV glycoproteins stimulate quite durable NAbs in mice, a result that correlates with our findings in mice of significant levels of anti-F protein splenic memory B cells and anti-F protein antibody-secreting bone marrow-associated plasma cells (41). Here we have shown a similar durability of anti-F protein antibody levels in cotton rats, as the levels of NAbs and total anti-F antibodies changed little during the 118 days after VLP immunization.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…An important property of vaccines is the durability of protective antibodies, but many vaccines do not result in a long duration of protection. We have previously reported that VLPs with RSV glycoproteins stimulate quite durable NAbs in mice, a result that correlates with our findings in mice of significant levels of anti-F protein splenic memory B cells and anti-F protein antibody-secreting bone marrow-associated plasma cells (41). Here we have shown a similar durability of anti-F protein antibody levels in cotton rats, as the levels of NAbs and total anti-F antibodies changed little during the 118 days after VLP immunization.…”
Section: Discussionsupporting
confidence: 92%
“…4B and C). Thus, anti-RSV F antibodies in dams do not decrease with time after VLP immunization, suggesting that the VLPs effectively stimulate cotton rat anti-F protein B cell memory and long-lived anti-F protein-secreting bone marrow-associated plasma cells induced by RSV priming, as we have previously suggested in murine studies (41). Serum titers in offspring of immunized dams.…”
Section: Durability Of Rsv Immune Responses In Damssupporting
confidence: 52%
“…Sera from each group of dams from each time point were pooled for determination of the total anti-pre-F IgG by ELISA. The levels of total anti-pre-F IgG antibodies increased significantly after a pre-F VLP or Post F VLP single immunization at day 70, as we have previously reported (18, 28, 31) (Figure 2, panels A and B) and remained relatively stable from day 141 to day 277 varying no more than 20%, with the exception of a drop at day 184 to between 43-58% of that on day 141 (Figure 2, Table 1). Day 184 was just before the delivery of the second breeding.…”
Section: Resultssupporting
confidence: 82%
“…In these studies, we have used RSV-primed animals in order to mimic normal human populations, most of which have been previously infected with RSV. We have reported that immunization of RSV-primed dams during pregnancy with pre-F VLPs resulted in robust protection of offspring from RSV challenge with no evidence of pathology (29-31). Here we describe the durability of these protective responses in dams after a single immunization and compare the degree of protection these dams can transfer to their offspring in two consecutive litters.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed novel virus-like particle (VLP) vaccine candidates for RSV [14][15][16][17][18]. In contrast to soluble proteins, VLPs robustly stimulate immune responses without the complications of adjuvant addition [19].…”
Section: Introductionmentioning
confidence: 99%